Recognition of Degraded Printed Gurmukhi Numerals- A Review - Goyal, Nishu; Garg, Seema (International Journal of Computer Sciences and Engineering, 2014)
OCR is optical character recognition. It is the prominent area of research in the world. It is translation of scanned images of handwritten, typewritten or printed document into machine encoded form. This machine encoded form is editable text and compact in size. OCR is a common method of digitizing printed texts so that they can be electronically searched, stored more compactly, displayed on-line, and used in machine processes such as machine, text-to-speech and text mining. Many OCRï¿½s have been designed which correctly identify fine printed documents both in Indian and foreign scripts. But little reported work has been found on the recognition of degraded Gurmukhi script. The performance of standard machine printed OCR system working for fine printed documents decreases, if it is tested on degraded documents [8]. The degradation in any document can be of many types. A major issue that leads in degraded printed numerals is heavily printed character, broken character, and background noise problem and shape variance character [10]. Although humans can read these documents easily, it is far complicated for computers to recognize them. So, our main focus will be to make the system recognize degraded printed Gurmukhi numerals.